Computer-Aided Rational Engineering of Signal Sensitivity of Quorum Sensing Protein LuxR in a Whole-Cell Biosensor - Li, Jinyu; Liu, Ruicun; Chen, Yulu; Liu, Shuxia; Chen, Cheng; Liu, Tuoyu; Yang, Shan; Zhuang, Yingtan; Yang, Ruifu; Cui, Yujun; Song, Yajun; Wang, Tao; et al. (Frontiers in Molecular Biosciences, 2021)
LuxR, a bacterial quorum sensing-related transcription factor that responds to the signaling molecule 3-oxo-hexanoyl-homoserine lactone (3OC6-HSL). In this study, we employed molecular dynamics simulation and the Molecular Mechanics Generalized Born Surface Area (MM-GB/SA) method to rationally identify residues in Vibrio fischeri LuxR that are important for its interaction with 3OC6-HSL. Isoleucine-46 was selected for engineering as the key residue for interaction with 3OC6-HSL-LuxR-I46F would have the strongest binding energy to 3OC6-HSL and LuxR-I46R the weakest binding energy. Stable wild-type (WT) LuxR, I46F and I46R variants were produced in Escherichia coli (E. coli) in the absence of 3OC6-HSL by fusion with maltose-binding protein (MBP). Dissociation constants for 3OC6-HSL from MBP-fusions of WT-, I46F- and I46R-LuxR determined by surface plasmon resonance confirmed the binding affinity. We designed and constructed a novel whole-cell biosensor on the basis of LuxR-I46F in E. coli host cells with a reporting module that expressed green fluorescent protein. The biosensor had high sensitivity in response to the signaling molecule 3OC6-HSL produced by the target bacterial pathogen Yersinia pestis. Our work demonstrates a practical, generalizable framework for the rational design and adjustment of LuxR-family proteins for use in bioengineering and bioelectronics applications.